The requirements for preparing the citizen’s budget and its reflections for activating government performance: An analytical study of views of a sample of citizens in the Duhok province - Mohamed Saleh, Ahmed; Abdullah, Ahmed (Humanities Journal of University of Zakho, 2021)
The research studying and analyzing the requirements for preparing the Citizen’s Budget and its reflection on activating the performance of the government sector. The research aims to address the public budget in the field of preparation, implementation and follow-up, and to address the concept of citizen’s budget as one of the concepts that have emerged recently and the importance of preparing it in strengthening community participation in the public budget.The research developed two hypotheses, the first of which is related to the existence of a statistically significant correlation relatuinship to the citizen’s budget requirements in activating government performance, and the second is the existence of a statistically significant moral effect of the citizen’s budget requirements in activating government performance. The most important conclusions reached by the researcher are the impact of the citizen’s budget requirements on the performance of the government and the existence of a relationship between the requirements of the citizen’s budget and the performance of the government in the Duhok province.The research reached a set of recommendations,the most important of which is the need to form a permament committee specialized in the accounting department prepares annually a manual about the Citizen’s Budget for the given year within the framework of the public budget approved by the legislative authority in order to achieve efficiency and performance by the government sector. To move towards participatory approach and community contribution to the preparation of the public budget.